GAMES IN TEACHING CHILDREN GRAMMAR - Krisdyawati, Ninit; Kustini, Siti (Politeknik Negeri Banjarmasin, 2011)
Nowadays Teaching English to Young Learners has become a trend. In every school, English is taught as one of the main subjects. Teaching young learners is different from teaching adults, children have their own way of learning. Since children like to play and have fun, the learning and teaching process should be suited with the nature of the chil-dren themselves. One of the forms of fun activities for children is through games. This study explored the effectiveness of games in improving studentsâ grammar competence in expressing degree of comparison and to find out studentsâ attitudes toward games. This study used a qualitative and quantitative approach employing one group pretest-posttest design of experimental research and open questionnaire for the data collection. The instrument of this study was a general test of English proficiency, a pretest, and a posttest. The general test was a standard and validated test based on the book âGames for Childrenâ by Gordon Lewis and Gunther Bedson (1999). Twenty multiple-choice items were selected from the book. One part was considered as the pretest, and the other one as the posttest. The results from the quantitative data showed that there was significant difference in the performance of the students after they received treatment with 95% degree of reliability. Meanwhile, the result from the qualitative data showed that fun learn-ing with games was perceived by the students positively. They expressed their frank opinion that learning English through games was fun. They felt happy when the lesson was delivered in a fun way since it could lower their anxiety. The results revealed that the language games used in this study were found to be effective in promoting learning of the comparative degree. Testing the selected before carrying it out in actual teaching was ad-visable. This was to enable the teacher to make necessary changes to ensure the smooth flow of the games.